Event attribution of Parnaíba River floods in Northeastern Brazil. Issue 1 (23rd August 2021) - Rudorff, Conrado; Sparrow, Sarah; Guedes, Marcia R. G.; Tett, Simon. F. B.; Brêda, João Paulo L. F.; Cunningham, Christopher; Ribeiro, Flávia N. D.; Palharini, Rayana S. A.; Lott, Fraser C.
Abstract: The climate modeling techniques of event attribution enable systematic assessments of the extent that anthropogenic climate change may be altering the probability or magnitude of extreme events. In the consecutive years of 2018, 2019, and 2020, rainfalls caused repeated flooding impacts in the lower Parnaíba River in Northeastern Brazil. We studied the effect that alterations in precipitation resulting from human influences on the climate had on the likelihood of flooding using two ensembles of the HadGEM3‐GA6 atmospheric model: one driven by both natural and anthropogenic forcings; and the other driven only by natural atmospheric forcings, with anthropogenic changes removed from sea surface temperatures and sea ice patterns. We performed hydrological modeling to base our assessments on the peak annual streamflow. The change in the likelihood of flooding was expressed in terms of the ratio between probabilities of threshold exceedance estimated for each model ensemble. With uncertainty estimates at the 90% confidence level, the median (5% 95%) probability ratio at the threshold for flooding impacts in the historical period (1982–2013) was 1.12 (0.97 1.26), pointing to a marginal contribution of anthropogenic emissions by about 12%. For the 2018, 2019, and 2020 events, the median (5% 95%) probability ratios at the threshold for flooding impacts were higher at 1.25 (1.07 1.46), 1.27 (1.12 1.445), and 1.37 (1.19 1.59), respectively; indicating that precipitation change driven by anthropogenic emissions has contributed to the increase of likelihood of these events by about 30%. However, there are other intricate hydrometeorological and anthropogenic processes undergoing long‐term changes that affect the flood hazard in the lower Parnaíba River. Trend and flood frequency analyses performed on observations showed a nonsignificant long‐term reduction of annual peak flow, likely due to decreasing precipitation from natural climate variability and increasing evapotranspiration and flow regulation. Abstract : We analyzed recent flooding events in the lower Parnaíba River using the Hadley Centre's event attribution modeling system and hydrological modeling. The results indicated that anthropogenic emissions have contributed to the increase of an impact‐related flooding event in Luzilândia in 2018, 2019 and 2020 by about 25, 27, and 37%. This study has important implications to help close research gaps in detection and attribution of riverine flood events affecting livelihoods in Northeastern Brazil.